A strong and flexible UV-resistant hardened film

By adding cellulose fiber polybenzotriazole composite to the hardened film, the problems of poor light resistance and easy precipitation of ultraviolet absorbers in the prior art are solved, and the excellent UV resistance of the hardened film is achieved. Long life and high mechanical properties.

CN115873289BActive Publication Date: 2025-02-11HEFEI LUCKY SCIENCE & TECHNOLOGY INDUSTRY COMPANY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211644738.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-21
Publication Date
2025-02-11
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

The existing ultraviolet cured hardened films have poor light resistance under ultraviolet light irradiation, which is prone to yellowing and cracking, and the ultraviolet absorber is easy to precipitate, affecting service life and cost.

Method used

Add cellulose fiber polybenzotriazole composite to the anti-glare coating of the hardened film to improve UV resistance and flexibility while maintaining high light transmittance and clarity.

Benefits of technology

The excellent UV resistance, long life and high mechanical properties of the hardened film are achieved, reducing costs and simplifying the formulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115873289B_ABST
    Figure CN115873289B_ABST
Patent Text Reader

Abstract

A highly flexible UV-proof hardened film, the hardened film comprises a transparent support and an anti-glare hardened layer coated on any surface of the transparent support; the anti-glare hardened layer is formed by curing and drying a coating liquid with UV light, the coating liquid comprises the following substances in parts by weight: 15 to 45 parts by weight of polyurethane acrylate oligomer; 5 to 30 parts by weight of cellulose fiber polybenzotriazole complex; 30 to 60 parts by weight of organic solvent; 0.01 to 2.5 parts by weight of leveling agent; 0.75 to 4.5 parts by weight of photoinitiator; wherein the cellulose fiber polybenzotriazole complex is composed of nano-scale cellulose fibers and nano-scale polybenzotriazole particles. The present invention adds a cellulose fiber polybenzotriazole complex to the anti-glare coating of the hardened film, so that the hardened film has excellent UV protection without reducing the curing effect of the coating, and has a light transmittance and clarity similar to that of a transparent film, and has excellent optical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-definition, highly flexible anti-ultraviolet curing film, belonging to the technical field of thin films. Background Art

[0002] At present, UV-cured hardened films utilize the photosensitivity of photoinitiators (photosensitizers) to form excited molecules under ultraviolet light, decompose into free radicals or ions, and thus make unsaturated organic matter undergo polymerization, grafting, cross-linking and other chemical reactions to achieve the purpose of curing and forming films. The better the UV light absorption during curing, the better the curing effect. However, in actual applications, hardened films are often used as protective films for outdoor display screens, car display screens, outdoor lamps, etc., and are often placed under ultraviolet light. Due to its mechanism, UV curing often makes the hardened film after light curing have poor light resistance, easy to turn yellow, crack, and seriously affect the lifespan and use effect. As a small molecule substance, the UV absorber is added to the coating liquid and is very easy to rise to the surface of the wet film during the drying stage in production, which seriously affects the photocuring reaction of the coating resin during the curing stage, causing the mechanical properties of the hardened film to deteriorate, affecting the use effect. At the same time, since most of the UV absorbers are distributed on the surface of the coating and do not participate in the reaction, they are particularly easy to precipitate and be scratched during the application process. It is also difficult to meet the life and performance requirements during use. They need to be replaced frequently, which greatly increases the cost.

[0003] In addition, due to the characteristics of light-cured hardened films and the generally used transparent supports, such as triacetyl cellulose (TAC), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC) and polymethyl methacrylate (PMMA), the flexibility is generally poor, and outdoor display screens, car display screens, outdoor lamps, etc. often have irregular shapes and curvatures, and ordinary hardened films are also difficult to apply to the surface. Compared with thermal curing and LED curing, UV-cured hardened films have excellent mechanical properties and are particularly used as protective films in these environments.

[0004] To this end, it is necessary to design a hardened film with good flexibility, not prone to yellowing, high light transmittance, good UV absorption performance and long service life, while not reducing the original mechanical properties of the hardened film. Summary of the invention

[0005] In order to overcome the drawbacks of the prior art, the present invention provides a highly flexible UV-proof hardened film, in which a cellulose fiber polybenzotriazole complex is added to the anti-glare coating of the hardened film, so that the hardened film has excellent UV protection without reducing the curing effect of the coating, and has a light transmittance and clarity that is close to transparent, and has excellent optical properties.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] A highly flexible UV-resistant hardened film, the hardened film comprising a transparent support and an anti-glare hardened layer coated on any surface of the transparent support; the anti-glare hardened layer is formed by curing and drying a coating liquid with UV light, and the coating liquid comprises the following substances in parts by weight:

[0008]

[0009] The cellulose fiber polybenzotriazole composite is composed of nano-scale cellulose fibers and nano-scale polybenzotriazole particles.

[0010] Polyurethane acrylate oligomer is a photosensitive resin with a relatively low molecular weight and has a group that can undergo a photocuring reaction. Among the various components of the photocurable product, polyurethane acrylate oligomer is the main body of the photocurable product, and its performance basically determines the main properties of the cured material, including physical and mechanical properties, flexibility, chemical resistance and yellowing resistance. When the content of polyurethane acrylate oligomer is less than 20 parts by weight, the coating thickness is thin, and the relative flexibility will be better, but the physical and mechanical properties such as hardness and wear resistance will be significantly deteriorated; when the content of polyurethane acrylate oligomer is higher than 45 parts, the coating thickness is high, and the flexibility of the hardened film is significantly deteriorated, which will have an adverse effect on the winding of the finished product and the warping of the sample will be larger, affecting the final use, but the physical and mechanical properties will be relatively significantly enhanced. Therefore, the content of polyurethane acrylate oligomer is 20 to 45 parts by weight, which is the most reasonable range of the present invention, because the use environment requires good flexibility, so the addition amount needs to be controlled.

[0011] The cellulose fiber polybenzotriazole compound plays a role in improving the flexibility of the hardened film, increasing the ultraviolet light absorption performance of the hardened film, ensuring that the hardened film does not turn yellow, increasing the outdoor service life, and improving the optical properties of the hardened film to ensure mechanical properties. If the amount of the cellulose fiber polybenzotriazole compound added is less than 5 parts, it will not provide sufficient flexibility and ultraviolet light absorption effect for the hardened film, and the set service life will not be achieved. When the amount of the cellulose fiber polybenzotriazole compound added is greater than 30 parts, although it can greatly enhance the flexibility and light resistance of the hardened film, the addition of a lot will affect the appearance of the sample, and affect the curing effect and mechanical properties. Therefore, the addition of nanospheres is in the appropriate range of 5 to 30 parts by weight, so that the flexibility, performance and appearance are comprehensively optimized.

[0012] Photoinitiator is a special catalyst for UV coatings. It is also an important component of UV coatings, which determines the photocuring rate of UV coatings and the photocuring degree of the final hardened film. If the photoinitiator is less than 0.75 parts by weight, the hardened film will not be completely cured, which will reduce the performance of the hardened film after curing, especially the physical properties and aging resistance. If the photoinitiator is higher than 4.5 parts by weight, although the hardened film will be completely cured and can ensure that the hardened film has a good curing effect, excessive addition of photoinitiator will cause the excess photoinitiator to not participate in the curing process, and thus remain in the hardened coating. There will be problems with small molecule precipitation in subsequent use, which will also have an adverse effect on the use of the hardened film.

[0013] When the coating liquid is applied in production or experiments, the coating liquid will have a process of flowing and drying to form a film. The wet coating film after wet coating can flow and eliminate the coating marks, and the degree of obtaining a uniform coating film after drying is called leveling. In actual operation, brush marks, roller marks, orange peel, shrinkage holes and other poor leveling phenomena often occur. The most effective way to overcome and prevent these drawbacks is to add a leveling agent. After adding the leveling agent, the wettability of the coating on the transparent support can be increased, the fluidity of the coating liquid can be improved, the leveling time can be extended, a monolayer can be formed on the surface of the coating film, and a uniform surface tension can be provided. It has a smooth and smooth effect, thereby improving the leveling of the coating film, and improving the smoothness and gloss. The leveling agents used for UV coatings are mainly polyacrylates, silicone resins and fluorosurfactants. If the amount of leveling agent added is low, the leveling effect is not good, and there will still be certain appearance problems; if the amount of leveling agent added is too much, it will have a certain degree of counter-effect on the appearance, and the probability of small molecules precipitating during use will be greatly increased, which will ultimately affect the use.

[0014] Organic solvents promote the even dispersion of the components in the coating liquid, the fluidity of the coating liquid during the production process, and reduce the viscosity of the coating liquid to improve processability. If the amount of organic solvent added is less than 30 parts, the coating liquid has a high solid content and a relatively large viscosity, the dispersion of the components in the coating liquid is poor, and the leveling of the coating liquid is also reduced to a certain extent, and various appearance problems are prone to occur during the production process. If the amount of organic solvent added is higher than 60 parts, although the dispersion of the components in the coating liquid is good, the fluidity of the coating liquid is good, and the processability is good, it will reduce the content ratio of oligomers in the coating liquid. Therefore, the amount of wet film is small during processing, and after UV curing and drying, the coating thickness is thin, which will affect the physical properties of the hardened film.

[0015] The above-mentioned highly flexible UV-resistant hardened film, in the cellulose fiber-polybenzotriazole composite, nanoscale cellulose fibers are the main body, and nanoscale polybenzotriazole particles are grafted onto the nanoscale cellulose fibers; the length of the nanoscale cellulose fibers is 0.5μm to 5μm, the diameter is 3nm to 500nm, the diameter of the nanoscale polybenzotriazole particles is 10nm to 300nm, and the N content in the cellulose fiber-polybenzotriazole composite is between 3.12% and 5.35%.

[0016] The size of nano-scale cellulose fibers is planned according to the flexibility set by the formula and as many grafted nano-scale polybenzotriazole particles as possible. If the length is less than 0.5μm, it is difficult to play the role of coating reinforcement after film formation, and the flexibility of the hardened film is difficult to meet the expected requirements; if the length is greater than 5μm, it is difficult to control the coating appearance, affecting the final use. At the same time, only when it reaches a certain length can it be guaranteed to load a certain amount of polybenzotriazole particles as a carrier. The diameter of nano-scale polybenzotriazole particles is between 10nm and 200nm. If the diameter is less than 10nm, the specific surface area is very large, and it is particularly easy to agglomerate. It is difficult to ensure the stability of the agglomerate after grafting. If the diameter is greater than 300nm, the diameter is relatively large relative to the nanofiber, and it is difficult to ensure that a sufficient amount of nano-scale polybenzotriazole is grafted. The N content of nano-scale cellulose fibers themselves is very low, and the N content of nano-scale polybenzotriazole particles is relatively high. If the N content of the cellulose fiber polybenzotriazole composite is significantly increased in the test, the composite is grafted with a certain amount of polybenzotriazole, thereby ensuring a good ultraviolet absorption effect.

[0017] The above-mentioned highly flexible UV-resistant hardened film, the preparation steps of the cellulose fiber polybenzotriazole composite include:

[0018] Step 1: Synthesis of polybenzotriazole nanoparticles;

[0019] Step 2: Surface modification of nano-scale cellulose fibers is performed through esterification reaction, so that -COOH is grafted onto the surface of the nano-fibers, and then polybenzotriazole nanoparticles are chemically grafted onto the surface to obtain the cellulose fiber-polybenzotriazole composite.

[0020] In the above-mentioned highly flexible UV-resistant hardened film, the polyurethane acrylate oligomer is one of an aliphatic polyurethane acrylate oligomer and an aromatic polyurethane acrylate oligomer; and the functionality of the polyurethane acrylate oligomer is 6-9.

[0021] There are urethane bonds in the polyurethane acrylate (PUA) molecule, which can form a variety of hydrogen bonds between polymer chains, so that the cured film has excellent wear resistance and flexibility, high elongation at break, good chemical resistance and high and low temperature resistance, good impact resistance, and good adhesion to plastic and other substrates. It is a very ideal main film-forming material in light-cured hardening film. When the functionality is less than 6, the cross-linking density is low, the flexibility is relatively good, but the hardness and wear resistance will be relatively poor, which affects the performance of the hardened film. When the functionality is higher than 9, the hardness and wear resistance of the film after formation are very good, but the flexibility is relatively poor, and the hardened film is hard and brittle, which affects the winding of the finished product during the production of the hardened film. Considering the flexibility and mechanical properties, the functionality of urethane acrylate oligomers is between 6 and 9.

[0022] The above-mentioned highly flexible UV-resistant hardened film, the leveling agent includes one or more of non-reactive polyether silicone, reactive polyether-modified silicone or reactive polyester-modified silicone, acrylate leveling agent, fluorine-modified acrylate copolymer agent.

[0023] The photoinitiator of the highly flexible UV-resistant hardened film is a free radical polymerization photoinitiator.

[0024] Free radical photoinitiators are mainly divided into two categories according to the different mechanisms of action of photoinitiators in generating active free radicals: cleavage-type free radical photoinitiators and hydrogen abstraction-type free radical photoinitiators. A cleavage-type free radical photoinitiator refers to a photoinitiator that analyzes and absorbs light energy and then transitions to an excited singlet state, and then to an excited triplet state through intersystem crossing. When it is in the excited singlet state or excited triplet state, the molecular structure is unstable, and the weak bonds therein will undergo homolytic cleavage to generate primary active free radicals, which will initiate the polymerization and crosslinking of oligomers and active diluents. A hydrogen abstraction-type photoinitiator refers to a photoinitiator that analyzes and absorbs light energy and then transitions to an excited triplet state through excitation and intersystem crossing, and then undergoes a bimolecular reaction with the co-initiator-hydrogen donor, generating active free radicals through electron transfer, which will initiate the polymerization and crosslinking of oligomers and active diluents.

[0025] The photoinitiator 184 selected in this paper is an α-hydroxyketone derivative among the cleavage-type free radical photoinitiators, and has good solubility in active diluents; λmax is at 246nm, 280nm and 333nm. After 184 absorbs light energy, it is cleaved to produce formyl radicals and hydroxycyclohexyl radicals, both of which are free radicals that initiate polymerization. There is no α-H at the ortho position of the benzoyl group in the molecular structure of 184, and it has very good thermal stability. There is no replacement of the benzyl structure during photolysis, and it has excellent yellowing resistance. It is also the most commonly used photoinitiator and the main initiator for photocurable coating liquids with high yellowing resistance requirements.

[0026] The above-mentioned highly flexible UV-resistant hardened film, the organic solvent is: a mixture of two or more of methyl isobutyl ketone, cyclohexanone, diisobutyl ketone, butyl acetate, ethyl acetate, isopropyl alcohol, isobutyl alcohol, propylene glycol monomethyl ether, butanone, toluene or xylene.

[0027] The above organic solvents can reduce the solid content of oligomers, make the ingredients in the formula evenly mixed together, improve the dispersibility of the coating liquid, especially the dispersibility of various organic, inorganic or mixed particles, reduce the agglomeration between particles, and improve the fluidity and coating appearance of the coating liquid during production. The organic solvent will select a single solvent or a mixed solvent with good solubility according to the formula ingredients and the coating appearance requirements during production.

[0028] The support of the above-mentioned highly flexible UV-resistant hardened film may be selected from one of triacetyl cellulose (TAC), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC) and polymethyl methacrylate (PMMA).

[0029] The above-mentioned support is a commonly used support in the hardening film industry and is well known in the industry. As a support for hardening film, it needs to have good mechanical properties such as tensile strength, elongation at break and elastic modulus; have certain impact strength and bending resistance; have certain aging resistance; have excellent optical properties such as surface gloss, refractive index and transparency; and the thickness of the support can be adjusted according to the needs of use.

[0030] Hardened films, especially anti-glare hardened films, will have a certain haze. The higher the haze, the better the anti-glare performance, so that the incident light forms "diffuse reflection" and the transmitted light forms "scattering", thereby reducing "glare stimulation" and improving the clarity of the display screen. The transmittance is the ratio of the luminous flux passing through the film material to the luminous flux irradiating the film, indicating the transparency of the film. The higher the clarity of the hardened film, the higher the transmittance.

[0031] The haze of the hardened film prepared by the present invention is between 0.5% and 10%, the transmittance is not less than 95%, and the clarity is not less than 93%; the flexibility of the hardened film can pass the GB / T 1731-2020 standard shaft rod 6, the length is about 35mm, the height is about 10mm, the thickness is 2mm, and the curvature radius R is (1.0±0.1)mm (diameter 2mm). Under this standard, there are 7 shaft numbers. The larger the shaft number, the better the flexibility and the greater the bending angle. Therefore, the hardened film is more suitable for uneven surfaces or curved surfaces.

[0032] The UV absorption rate of the hardened film prepared by the present invention is 98% at a wavelength of 380nm, and the average UV absorption rate in the range of 360nm to 400nm is 95%. The higher the UV absorption rate, the better the UV protection effect.

[0033] The hardened film prepared by the present invention is resistant to light exposure for 5000 hours (irradiation energy: 60w / m 2 , 300-400nm) after the b value changes △b <0.5%. When the general hardened film is tested for light resistance, the coating will turn yellow, that is, the b value changes greatly before and after the test, and the various properties of the hardened film will be significantly deteriorated. When the b value changes within a certain range, the longer the test time, the better the light resistance of the hardened film and the longer the service life.

[0034] The beneficial effects of the present invention are:

[0035] 1. The present invention uses nanocellulose as a carrier. Compared with the traditional addition of ultraviolet absorbers, it can graft as many polybenzotriazole nanoparticles as possible. Compared with small molecule ultraviolet absorbers, the cellulose fiber polybenzotriazole complex ensures a certain molecular weight, so that the complex is located inside the coating as much as possible, so that the hardened film has excellent ultraviolet protection without reducing the curing effect of the coating.

[0036] 2. The present invention uses nanocellulose to graft polybenzotriazole nanoparticles, that is, the nanoparticles are fixed on the fibers to form a larger complex. The steric hindrance and the resistance between the complexes are large. There is no need to worry about the agglomeration of the nanoparticles, and there is no need to adjust the formula by adding a dispersant. The formula is simplified, and the possibility of small molecule precipitation is further reduced.

[0037] 3. The present invention has a relatively small amount of cellulose fiber polybenzotriazole composite located on the upper part and the surface of the coating, so that the hardened film has a certain haze. Since cellulose and polybenzotriazole are nano-scale organic substances, the refractive index is close to that of the coating, so that the overall light transmittance and clarity of the hardened film are very high, very close to transparent, so that the hardened film has a certain anti-glare effect, and has a light transmittance and clarity similar to transparent, and has excellent optical properties.

[0038] 4. In the present invention, polybenzotriazole is used as a UV absorber. Compared with directly adding the UV absorber, the nanocellulose grafted polybenzotriazole nanoparticles can be added in larger amounts and are basically located inside the coating. There is no need to worry about more losses during use like general UV absorbers located on the surface of the coating. The light resistance is very excellent, the test time is longer than that of traditional UV-resistant hardened films, and the b value of the coating changes very little. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings are not intended to be drawn to scale. In the drawings, each identical or nearly identical component shown in various figures may be represented by the same reference numeral. For clarity, not every component is labeled in every figure. Embodiments of various aspects of the present invention will now be described by way of example and with reference to the accompanying drawings, in which:

[0040] Figure 1 is a schematic diagram of the structure of a cellulose fiber polybenzotriazole composite;

[0041] Figure 2 It is a schematic diagram of the cross-sectional structure of the present invention.

[0042] In the figure, 1. transparent support; 2. anti-glare layer; 3. cellulose fiber polybenzotriazole composite. DETAILED DESCRIPTION

[0043] The cellulose fiber polybenzotriazole composite of the present invention is organic and has a refractive index very close to that of the coating resin, so the hardened film has very good light transmittance and clarity. Nanocellulose fibers can be grafted with more nano polybenzotriazole particles, so that the overall molecular weight of the composite is greatly improved. Compared with adding the same amount of nano polybenzotriazole small particles, adding composite macromolecules is more likely to remain in the coating rather than migrate to the coating surface with solvent volatilization. The higher the molecular weight of the composite, the more nanoparticles are grafted, and there is no need to add too much composite to ensure ultraviolet absorption performance. However, if there is too much grafting, the more nanoparticles there are, a small amount of composite can achieve the desired ultraviolet absorption performance, but the fiber ratio is reduced, and the improvement in flexibility is not as strong as before. Therefore, the molecular weight or grafting amount needs to be controlled within a certain range. The amount of grafting is determined by testing the N content in the cellulose fiber polybenzotriazole composite. Cellulose basically does not contain N elements. After grafting polybenzotriazole nanoparticles, the entire composite contains N elements. When the measurement range of the N element is between 3.12% and 5.35%, the amount of grafting reaches the requirement of the present invention.

[0044] In the process of solvent volatilization at high temperature, since we choose a combination of solvents, the volatilization rate of the solvents is different, which is equivalent to different solvents volatilizing at different stages during the entire drying time, rather than all solvents volatilizing together. In this way, compared with further dispersing the lift provided by the solvent, even if there is no dispersion, the lift provided by the solvent volatilization is also within a certain range. When the mass of the particles reaches a certain level, the lift provided by the solvent volatilization is not enough to bring the particles to the coating surface. Therefore, when the composite reaches a certain molecular weight, the mass of the unit composite is large enough to make more composites located inside the coating and minimize the movement of nano-polybenzotriazole particles to the coating surface. Under the same unit mass conditions, the larger the particle size, the greater the lift brought by the solvent volatilization, and the smaller the size, the opposite. The cellulose fiber polybenzotriazole composite is at the nanoscale, and the lift it is naturally subjected to is minimized. The two aspects work together to make the composite located inside the coating as much as possible, thereby reducing the light curing effect of the coating and reducing the consumption of the ultraviolet absorber on the surface during use. The cellulose fiber in the coating can be regarded as a reinforcement of the coating, which can effectively enhance the flexibility of the coating.

[0045] The preparation steps of the cellulose fiber polybenzotriazole composite include:

[0046] Step 1: Synthesis of polybenzotriazole nanoparticles:

[0047] In the case of sodium dodecylbenzene sulfonate as a surfactant and potassium persulfate as an initiator, the polybenzotriazole nanoparticles are prepared by emulsion copolymerization of vinyl monomer 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole and crosslinking monomer divinylbenzene. Specifically, 95 mL of a toluene solution containing 16.85 g of the vinyl monomer 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole is added to 240 mL of an aqueous solution containing 3.4 g of sodium dodecylbenzene sulfonate, 350 μL of divinylbenzene and 1.12 g of potassium persulfate; the mixture is stirred at 85° C. for 24 hours; and then impurities and solvents are removed by centrifugation, filtration, drying and other steps to obtain pure polybenzotriazole nanoparticles, wherein the diameter of the nanoscale polybenzotriazole particles is between 10 nm and 300 nm.

[0048] Step 2: Surface modification of nano-scale cellulose fibers is performed through an esterification reaction, so that -COOH is grafted onto the surface of the nano-fibers, and then polybenzotriazole nanoparticles are chemically grafted onto the surface to obtain the cellulose fiber-polybenzotriazole composite:

[0049] Na2CO3 was added to adjust the pH of 40g CNF deionized water solution (1wt%) to 8.0-9.0. The mixture was solvent exchanged twice with acetone and ethanol, and the CNF was separated and redispersed in dimethyl sulfoxide using a centrifuge, and the suspension was transferred to a three-necked flask. Then, 4.5g of polybenzotriazole nanoparticles were directly added to the flask and reacted with the CNF suspension at 90°C under continuous magnetic stirring for 5 hours. During the reaction, the flask was kept in a nitrogen atmosphere. After the reaction, the mixture was treated with a large amount of acetone, ethanol washing, filtration, centrifugation, etc. to obtain a cellulose fiber polybenzotriazole composite. The chemical reagent is preferably selected from McLean and Sigma-Aldrich, and the weight proportion of the dicellulose fiber polybenzotriazole composite is 5-30 parts, preferably 2-25 parts, and more preferably 7.5-20 parts.

[0050] In the present invention, the polyurethane acrylate resin is an aromatic or aliphatic polyurethane acrylate with a functionality between 6 and 9; the weight of the polyurethane acrylate is 15 to 45 parts, preferably 15 to 40 parts, and more preferably 25 to 35 parts. Specifically, in the embodiment of the present invention, CN 997 of Sartomer, EB2220 of Allnex, SU-88 of Qiti, 6146-100 of Changxing, UV 2600 of Qianyou, L-6604 of Sanqi, and LT6160 of Guangxin can be used.

[0051] In the present invention, the leveling agent preferably includes one or more of non-reactive polyether silicone, reactive polyether-modified silicone or reactive polyester-modified silicone, acrylate leveling agent, and fluorine-modified acrylate copolymer agent. Different types of leveling agents have different effects. Acrylate leveling agents can improve the leveling of the coating, thereby further reducing the flash point of the anti-glare film. Silicone leveling agents can not only improve the leveling of the coating, but also contain silicone and have a small particle size. They will agglomerate with nanoparticles, increase the particle size to a certain extent, and increase the haze of the anti-glare film to a certain extent. The weight of the leveling agent is 0.01 to 2.5 parts, preferably 0.05 to 2 parts, and more preferably 0.5 to 2 parts. Specifically, in the embodiments of the present invention, BYK370, BYK3570, BYK354 or BYK350 leveling agent produced by BYK Chemicals, TEGO Flow425, TEGO Glide440 or TEGO ZFS 460 produced by Evonik may be used.

[0052] In the present invention, the photoinitiator is a free radical polymerization photoinitiator, such as: 1-hydroxycyclohexyl phenyl ketone (184), 2-methyl-1-(4-methylthiophenyl)-2-morpholinyl-1-propanone (907), benzoin dimethyl ether (651), 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide (TPO) or 2-isopropylthioxanthone (ITX). The photocuring agent can be used alone or in combination of two or more. The amount of the photoinitiator added is 1.5 to 8.5 parts, preferably 3.5 to 7 parts, and more preferably 4.5 to 6.5 parts.

[0053] In order to ensure that the solvent of the coating is quickly volatilized completely when entering the oven for drying, the organic solvent is a mixture of two or more of methyl isobutyl ketone, cyclohexanone, diisobutyl ketone, butyl acetate, ethyl acetate, isopropanol, isobutyl alcohol, propylene glycol monomethyl ether, butanone, toluene or xylene. The amount of the organic solvent added is 20 to 70 parts.

[0054] As long as a coating can be formed, the present invention has no clear limitation on the coating method, and conventional coating methods can be used, including rod coating, knife coating, blade coating, gravure coating, roll coating, slot coating and Mayer rod coating to form a coating. Rod coating and gravure coating are preferred.

[0055] In the present invention, there is no particular limitation on the material of the transparent support, and any transparent support known in the art can be used. Preferably, the support can be selected from one of triacetyl cellulose (TAC), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC) and polymethyl methacrylate (PMMA).

[0056] The present invention will be further described below in conjunction with the embodiments.

[0057] Example 1

[0058]

[0059]

[0060] 25 parts by weight of polyurethane acrylate (CN 997 from Sartomer) was added to 62.5 parts by weight of solvent (24.5 parts by weight of propylene glycol monomethyl ether, 22 parts by weight of ethyl acetate and 16 parts by weight of butanone), and the mixture was dissolved and stirred evenly. 0.5 parts by weight of polyether silicone leveling agent (BYK-370 from Sartomer) and 4.5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added and stirred evenly. Finally, 10 parts by weight of cellulose fiber polybenzotriazole complex was added and dispersed at high speed for 30 minutes at a stirring speed of 1200 r / min.

[0061] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0062] Example 2

[0063]

[0064] 35 parts by weight of polyurethane acrylate (EB 2200 from Allnex) was added to 26.5 parts by weight of solvent (14 parts by weight of propylene glycol monomethyl ether, 12.5 parts by weight of ethyl acetate), and the mixture was dissolved and stirred evenly. 2 parts by weight of polyether silicone leveling agent (BYK-3570 from Sabic) and 6.5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added and stirred evenly. Finally, 20 parts by weight of cellulose fiber polybenzotriazole complex was added and dispersed at high speed for 50 minutes at a stirring speed of 1200 r / min.

[0065] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0066] Example 3

[0067]

[0068] Add 30 parts by weight of polyurethane acrylate (SU-88 from Qiti) to 54 parts by weight of solvent (20 parts by weight of propylene glycol monomethyl ether, 18 parts by weight of ethyl acetate and 16 parts by weight of butanone), dissolve and stir evenly. Continue to add 1 part by weight of polyether silicone leveling agent (BYK-350 from Shabi) and 5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone, stir evenly. Finally, add 10 parts by weight of cellulose fiber polybenzotriazole complex and stir and disperse at high speed for 30 minutes at a stirring speed of 1200r / min.

[0069] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0070] Example 4

[0071]

[0072] Add 30 parts by weight of polyurethane acrylate (6146-100 from Changxing Company) to 46.5 parts by weight of solvent (19 parts by weight of propylene glycol monomethyl ether, 17.5 parts by weight of ethyl acetate and 10 parts by weight of butanone), dissolve and stir evenly. Continue to add 1.5 parts by weight of polyether silicone leveling agent (TEGO ZFS460 from Evonik Company) and 6 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone, stir evenly. Finally, add 15 parts by weight of cellulose fiber polybenzotriazole complex and stir and disperse at high speed for 30 minutes at a stirring speed of 1200r / min.

[0073] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0074] Example 5

[0075]

[0076] 25 parts by weight of polyurethane acrylate (LT6160 from Changxing Company) were added to 53 parts by weight of solvent (22 parts by weight of propylene glycol monomethyl ether, 18 parts by weight of ethyl acetate and 12 parts by weight of butanone), dissolved and stirred evenly. 1.5 parts by weight of polyether silicone leveling agent (TEGO Glide4400 from Evonik Company) and 5.5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added, and stirred evenly. Finally, 15 parts by weight of cellulose fiber polybenzotriazole complex was added and dispersed at high speed for 40 minutes at a stirring speed of 1200 r / min.

[0077] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0078] Example 6

[0079]

[0080] 35 parts by weight of polyurethane acrylate (UV 2600 from Qianyou Company) was added to 47.5 parts by weight of solvent (20 parts by weight of propylene glycol monomethyl ether, 17.5 parts by weight of ethyl acetate and 10 parts by weight of butanone), dissolved and stirred evenly. 2 parts by weight of polyether silicone leveling agent (TEGO ZFS460 from Evonik Company) and 5.5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added and stirred evenly. Finally, 10 parts by weight of cellulose fiber polybenzotriazole complex was added and dispersed at high speed for 30 minutes at a stirring speed of 1200 r / min.

[0081] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0082] Comparative Example 1

[0083]

[0084] 25 parts by weight of polyurethane acrylate (CN 997 from Sartomer) were added to 62.5 parts by weight of solvent (24.5 parts by weight of propylene glycol monomethyl ether, 22 parts by weight of ethyl acetate and 16 parts by weight of butanone), dissolved and stirred evenly. 0.5 parts by weight of polyether silicone leveling agent (BYK-370 from Sartomer) and 4.5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added, and stirred evenly. Finally, 4 parts by weight of nanocellulose fibers and 3.5 parts by weight of separately synthesized nano polybenzotriazole particles were added and dispersed at high speed for 30 minutes at a stirring speed of 1200 r / min.

[0085] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0086] Comparative Example 2

[0087]

[0088]

[0089] 35 parts by weight of polyurethane acrylate (EB 2200 from Allnex) was added to 26.5 parts by weight of solvent (14 parts by weight of propylene glycol monomethyl ether, 12.5 parts by weight of ethyl acetate), dissolved and stirred evenly. 2 parts by weight of polyether silicone leveling agent (BYK-3570 from Sabic) and 6.5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added and stirred evenly. Finally, 10 parts by weight of nanocellulose fibers and 10 parts by weight of separately synthesized nano-polybenzotriazole particles were added and dispersed at high speed for 50 minutes at a stirring speed of 1200 r / min.

[0090] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0091] Comparative Example 3

[0092]

[0093] 30 parts by weight of polyurethane acrylate (SU-88 from Qiti) was added to 54 parts by weight of solvent (20 parts by weight of propylene glycol monomethyl ether, 18 parts by weight of ethyl acetate and 16 parts by weight of butanone), dissolved and stirred evenly. 1 part by weight of polyether silicone leveling agent (BYK-350 from Sabic) and 5 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added, and stirred evenly. Finally, 2.5 parts by weight of nanocellulose fibers and 7.5 parts by weight of separately synthesized nano-polybenzotriazole particles were added and dispersed at high speed for 30 minutes at a stirring speed of 1200 r / min.

[0094] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0095] Comparative Example 4

[0096]

[0097] 30 parts by weight of polyurethane acrylate (6146-100 from Changxing Company) were added to 46.5 parts by weight of solvent (19 parts by weight of propylene glycol monomethyl ether, 17.5 parts by weight of ethyl acetate and 10 parts by weight of butanone), dissolved and stirred evenly. 1.5 parts by weight of polyether silicone leveling agent (TEGO ZFS460 from Evonik Company) and 6 parts by weight of photoinitiator 1-hydroxycyclohexyl phenyl ketone were added and stirred evenly. Finally, 12.5 parts by weight of nanocellulose fibers and 2.5 parts by weight of separately synthesized nano polybenzotriazole particles were added and dispersed at high speed for 30 minutes at a stirring speed of 1200 r / min.

[0098] The coating liquid was applied to one side of an optical grade polytriacetyl cellulose film (TAC film) with a thickness of 80 μm using a wire rod coater, and then placed in a 50°C oven. The oven was raised to 70°C for 1.5 min, and the dried coating was cured by ultraviolet irradiation. The irradiation amount of ultraviolet light was 750 mJ / cm 2 The prepared hardened film was obtained. The haze transmittance, clarity, bending resistance, UV absorption rate, b value change rate after 5000h light resistance and coating appearance were tested.

[0099] The performance test methods are as follows;

[0100] (1) Haze transmittance test

[0101] The haze transmittance was tested using a haze meter (Nippon Denshoku Corporation; model: NDH2000N).

[0102] (2) Clarity test

[0103] Determined according to the method specified in ASTM D1003, haze meter (BYK, model: 4725)

[0104] (3) Ultraviolet absorbance, b value measurement

[0105] Spectrophotometer (Konica Corporation, Japan, model: CM-5)

[0106] (4) Bending resistance

[0107] The test was carried out according to the method specified in GB / T 1731-2020, using a paint film flexibility tester.

[0108] Shaft rod 1: Length about 35mm, diameter

[0109] Shaft rod 2: length is about 35mm, diameter

[0110] Shaft rod 3: length is about 35mm, diameter

[0111] Shaft rod 4: length is about 35mm, diameter

[0112] Shaft rod 5: length is about 35 mm, height is about 10 mm, thickness is 3 mm, curvature radius R is (1.5±0.1) mm (diameter Φ is 3 mm);

[0113] Shaft rod 6: length is about 35 mm, height is about 10 mm, thickness is 2 mm, curvature radius R is (1.0 ± 0.1) mm (diameter Φ is 2 mm);

[0114] Shaft rod 7: length is about 35 mm, height is about 10 mm, thickness is 1 mm, and curvature radius R is (0.5±0.1) mm (diameter Φ is 1 mm).

[0115] (5) Adhesion

[0116] Determined according to the method specified in GB / T 33049-2016.

[0117] (6)Light resistance

[0118] Xenon lamp aging test instrument (Dongguan Liuqin Testing Instrument Co., Ltd., model: LQ-XD-512)

[0119] (7) Wear resistance test

[0120] The scratch resistance of the anti-glare layer was measured according to the method specified in HG / T 4303, with a load of 500g and 100 cycles of friction.

[0121] (8) Observation

[0122] Select 10 people to observe the texture of the sample with naked eyes, visually observe the texture of the sample such as clarity, the crystal point defects of the sample and the coating appearance of the sample, and combine the results of the 10 people and record them as follows:

[0123] The sample has good clarity, normal appearance, no crystal points, silk bar marks, no "powder falling" and other problems, and is recorded as "○";

[0124] The sample has average clarity, normal appearance, many crystal points, local flowery spots, and slight silk bar marks and powder loss. Record as "△";

[0125] The sample has poor clarity, poor appearance, many crystal points, large area of ​​​​flowering, and heavy silk bar printing and "powder loss". Recorded as "×". The test results are shown in Table 1:

[0126] Table 1 Test results of embodiments and comparative examples

[0127]

[0128] As can be seen from Table 1, the experimental results show that the comprehensive performance of the hardened film prepared by Examples 1 to 6 of the present invention is excellent, the haze is between 1.52% and 8.73%, the transmittance is not less than 95%, and the clarity is greater than 96%; the flexibility can pass the shaft rod 6 after the flexibility tester test, and Examples 2 and 5 can reach the best standard shaft rod 7. The ultraviolet absorption rate at 380nm is above 96% in the six embodiments, and the highest is close to 99%. The ultraviolet performance is very good. The average ultraviolet absorption rate at 360-400nm is above 94%, and the highest is close to 97%, and the performance is also very good. After the wear test, the wear problem occurred during the simulated use. The ultraviolet absorption rate at 380nm changed very little. Because the ultraviolet absorber is located inside the coating as much as possible, the absorption rate is basically above 96%, and the average absorption rate at 360-400nm is also maintained at above 94%, which has both excellent wear resistance and ultraviolet absorption performance. For hardened film products, the adhesion performance of the coating to the substrate is very important, which seriously restricts the use effect and life. In Examples 1 to 6, the adhesion can reach 100%, which does not affect the use at all. At the same time, because of the good adhesion and UV absorption performance, the hardened film can be supported for a longer time in the light resistance test, and the b value change rate is very small, so the yellowing change is very slow during use, which improves the use effect and service life. The appearance of Examples 1 to 6 is good, the clarity is good, the appearance is normal, there is no crystal point, silk bar printing, no "powder falling" and other problems.

[0129] Comparing Example 1 with Comparative Example 1, Example 2 with Comparative Example 2, Example 4 with Comparative Example 3, and Example 6 with Comparative Example 4, when the haze is similar, the light transmittance and clarity of the comparative example are much different from those of the examples, because the comparative example directly adds nanoparticles and nanofibers, which have low molecular weight and low unit mass, and are very easily lifted to the coating surface by the lift provided by the solvent volatilization, thereby causing more light scattering and diffuse reflection, which reduces the light transmittance and clarity. This problem not only affects the appearance problem, but also easily causes the nanoparticles and nanofibers to agglomerate to form larger crystal points, which not only affects the ultraviolet absorption effect compared to the examples, but also reduces the light transmittance and clarity. Moreover, the nano-polybenzotriazole particles are located on the surface of the coating. Compared with the examples, although the ultraviolet absorption performance of the hardened film is not significantly reduced, it is precisely because the surface layer absorbs a large amount of UV energy, which makes it difficult for the inside and bottom of the coating to obtain sufficient UV energy, resulting in incomplete curing of the coating, which directly affects the adhesion performance of the coating. Therefore, the adhesion performance of the comparative example is very different from that of the examples, and generally the industry requires that it must reach 100%. The coating is poorly cured, and the particles are easily worn off on the surface, resulting in a sharp drop in UV absorption performance compared to the example after the wear test. This is still the case under the relatively low requirements of this test within the industry standard. If a higher load and more times are tested, the deterioration will be more obvious, seriously affecting the use effect and life. Due to adhesion problems and curing degree problems, even if the UV absorption performance of the comparative example is good, during the light resistance test, the coating and surface particles are particularly easy to fall off, which also affects the test results, and the b value changes are very obvious.

[0130] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly flexible UV-resistant hardened film, comprising a transparent support and an anti-glare hardened layer coated on any surface of the transparent support; characterized in that: The anti-glare hardened layer is formed by curing a coating liquid with ultraviolet light and drying the coating liquid, wherein the coating liquid comprises the following substances in parts by weight: 15-45 parts by weight of polyurethane acrylate oligomer; 5 to 30 parts by weight of cellulose fiber polybenzotriazole composite; 30-60 parts by weight of an organic solvent; Leveling agent 0.01-2.5 parts by weight; 0.75-4.5 parts by weight of photoinitiator; Wherein, the cellulose fiber polybenzotriazole composite is composed of nano-scale cellulose fibers and nano-scale polybenzotriazole particles; The preparation steps of the cellulose fiber polybenzotriazole composite include: Step 1: Synthesizing polybenzotriazole nanoparticles; preparing polybenzotriazole nanoparticles by emulsion copolymerization of vinyl monomer 2-(2'-hydroxy-5'-methacryloxyethylphenyl)-2H-benzotriazole and crosslinking monomer divinylbenzene in the presence of sodium dodecylbenzene sulfonate as a surfactant and potassium persulfate as an initiator; Step 2: Surface modification of nano-scale cellulose fibers is performed through esterification reaction, so that -COOH is grafted onto the surface of the nano-fibers, and then polybenzotriazole nanoparticles are chemically grafted onto the surface to obtain the cellulose fiber-polybenzotriazole composite.

2. The highly flexible UV-resistant hardened film according to claim 1, characterized in that: The length of the nano-scale cellulose fiber is 0.5 μm to 5 μm, the diameter is 3 nm to 500 nm, the diameter of the nano-scale polybenzotriazole particles is 10 nm to 300 nm, and the N content in the cellulose fiber polybenzotriazole composite is between 3.12% and 5.35%.

3. The highly flexible UV-resistant hardened film according to claim 1, characterized in that: The polyurethane acrylate oligomer is one of an aliphatic polyurethane acrylate oligomer and an aromatic polyurethane acrylate oligomer; and the functionality of the polyurethane acrylate oligomer is 6-9.

4. The highly flexible UV-resistant hardened film according to claim 1, characterized in that: The leveling agent includes one or more of non-reactive polyether silicone, reactive polyether-modified silicone or reactive polyester-modified silicone, acrylate leveling agent, and fluorine-modified acrylate copolymer agent.

5. The highly flexible UV-resistant hardened film according to claim 1, characterized in that: The photoinitiator is a free radical polymerization photoinitiator.

6. The highly flexible UV-resistant hardened film according to claim 1, characterized in that: The organic solvent is a mixture of two or more of methyl isobutyl ketone, cyclohexanone, diisobutyl ketone, butyl acetate, ethyl acetate, isopropanol, isobutanol, propylene glycol monomethyl ether, butanone, toluene or xylene.

7. The highly flexible UV-resistant hardened film according to claim 1, characterized in that: The support is selected from one of triacetyl cellulose (TAC), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC) and polymethyl methacrylate (PMMA).

Citation Information

Patent Citations

  • Anti-ultraviolet anti-glare coating film and applications thereof

    CN108690209A